2011
DOI: 10.1007/s00468-011-0574-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient changes in transpiration, and stem and soil CO2 efflux in longleaf pine (Pinus palustris Mill.) following fire-induced leaf area reduction

Abstract: In 20-year-old longleaf pine, we examined short-term effects of reduced live leaf area (A L ) via canopy scorching on sap flow (Q; kg H 2 O h -1 ), transpiration per unit leaf area (E L ; mm day -1 ), stem CO 2 efflux (R stem ; lmol m -2 s -1 ) and soil CO 2 efflux (R soil ; lmol m -2 s -1 ) over a 2-week period during early summer. R stem and Q were measured at two positions (1.3-m or BH, and base of live crown-BLC), and R soil was measured using 15 opensystem chambers on each plot. E L before and after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Statistically, our data on sap flow reached the lowest limit. In line with our results, Clinton et al (2011) did not find any change in sap flow of longleaf pine (P. palustris Mill.) after fire-induced leaf area reduction.…”
Section: Stem Co 2 Effluxsupporting
confidence: 94%
See 1 more Smart Citation
“…Statistically, our data on sap flow reached the lowest limit. In line with our results, Clinton et al (2011) did not find any change in sap flow of longleaf pine (P. palustris Mill.) after fire-induced leaf area reduction.…”
Section: Stem Co 2 Effluxsupporting
confidence: 94%
“…Previous studies have reported that changes in carbohydrate availability, which are caused by increasing atmospheric CO 2 concentration (Edwards et al 2002;Wertin and Teskey 2008), girdling (Maier et al 2010;Maunoury-Danger et al 2010), fire (Clinton et al 2011), and phloem chilling (Johnsen et al 2007), can significantly modify the stem CO 2 efflux within several days. Furthermore, pruning has the potential to influence stem CO 2 efflux by altering canopy transpiration, because CO 2 is transported via transpiration stream from soil or the lower part of the stem to the canopy .…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore likely that carbon supply and demand is balanced in young trees of fast growing species such as P. × canadensis , so that stored carbon pools might be minimal to maintain cell growth and maintenance processes under unfavourable scenarios (Sala et al ., ). As a result, coupling between stem respiration and carbon supply is often observed when phloem transport is altered via stem girdling, canopy scorching or inhibition of photosynthesis (Wertin & Teskey, ; Maier et al ., ; Maunoury‐Danger et al ., ; Clinton et al ., ; De Schepper & Steppe, ; Bloemen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…A two‐thirds defoliation was initially tested, but eventually the percentage of leaf area removal was increased due to the slight effect observed on sap flow at two‐thirds defoliation (probably explained by stomatal compensation; e.g. Maier & Clinton, ; Clinton et al ., ). The DEF 2 treatment consisted of 100% leaf area removal.…”
Section: Methodsmentioning
confidence: 97%
“…Likewise, Vogel and Valentine [8] suggest that measurements of R s from small root exclusion tubes within three weeks of installation may mitigate effects of root exclusion on soil moisture. However, three weeks of post-treatment incubation was insufficient to detect R h in longleaf pine, perhaps because of greater carbohydrate stores in longleaf pine roots relative to other species [24,25]. We suggest that the longer incubation did not profoundly change soil moisture dynamics or our overall estimate of R h to R s , because soils in this study were sandy with excessive drainage and the presence of the root exclusion tubes increased soil moisture on the final measurement date by only about 1%.…”
Section: Discussionmentioning
confidence: 99%